The effects of RYSEN-induced supportive, propelling and impeding forces on step parameters and muscular control in walking after stroke - Sanne Ettema; Tom J. W. Buurke; Sina David; Coen A. M. van Bennekom; Han Houdijk (PLoS ONE, 2025)
Background Body weight support (BWS) devices are increasingly used for gait training after stroke. The RYSEN not only allows for vertical BWS but also for the addition of mediolateral and anteroposterior forces. To assess to what extent the RYSEN could be used for targeted gait training, this study aimed to investigate the effect of BWS with and without the addition of mediolateral and anteroposterior forces on step parameters and muscular control in individuals after stroke and able-bodied individuals. Methods In this cross-sectional study, fifteen individuals after stroke and fifteen able-bodied individuals completed several overground walking conditions: unsupported and BWS with(out) mediolateral and anteroposterior forces. Step length, step width (variability), single stance time and walking speed were determined using motion capture data. Muscular control was assessed using electromyography. Linear mixed-effect models were used to analyze the (interaction) effects of condition and group on step parameters. Statistical parametric mapping was used to analyze muscular control. Findings Providing BWS led to increased speed and balance confidence in individuals after stroke, and caused decreased speed, step width variability and m. Gluteus Medius activity in able-bodied individuals. Adding mediolateral forces did not lead to additional changes. Adding anterior forces increased speed in individuals after stroke. Adding posterior forces slightly increased plantar flexor activity during push-off in able-bodied individuals. Interpretation RYSEN BWS facilitates gait training at increased speed and balance confidence. Adding mediolateral or anteroposterior forces did not provide strong additional effects. Further research may determine how these forces can be better utilized during training.